A Novel Method of Water Mist Bonding for Manufacturing Biological Gel Artificial Muscle with High Actuation Performance. Issue 12 (1st December 2022) - Wang, Junyao; Lang, Tianhong; Liu, Huan; Chen, Yansong; Cui, Bowen; Wang, Rui
Abstract : Biological gel artificial muscle (BGAM) has a promising future in the field of MEMS. In contrast to the material research of BGAM, relatively little research is conducted on the preparation process method of BGAM. Therefore, a water mist bonding method for the preparation of BGAM is proposed. The main application of the water mist bonding method is to complete the assembly of the electrode membrane with the electrically actuated membrane, and the actuation properties of the BGAM can be further enhanced. In this paper, experiments on mechanical, electrical, and actuation properties are conducted to investigate the effects of the water mist bonding process parameters on BGAM. The comprehensive experimental results revealed that BGAM possessed a more comprehensive optimization effect when the humidification time is 2.5 min: the bond strength reached the highest 0.92 MPa, the internal resistance, and elastic modulus are significantly reduced to 28 Ω and 2.08 MPa, respectively, and the output force response rate reached the highest 0.138 mN s −1 . In conclusion, the water mist bonding process proposed does not require complicated equipment, features optimized BGAM actuation performance, and makes up for the lack of process methods for preparing BGAM at this stage.